Epsin but not AP-2 supports reconstitution of endocytic clathrin-coated vesicles - Brod, Jan; Hellwig, Andrea; Wieland, Felix T. (FEBS letters, 2020)
Formation of clathrin-coated vesicles (CCVs) in receptor-mediated endocytosis is a mechanistically well-established process, in which clathrin, the adaptor protein complex AP-2, and the large GTPase dynamin play crucial roles. In order to obtain more mechanistic insight into this process, here we established a giant unilamellar vesicle (GUV)-based in vitro CCV reconstitution system with chemically defined components and the full-length recombinant proteins clathrin, AP-2, epsin-1, and dynamin-2. Our results support the predominant model in which hydrolysis of GTP by dynamin is a prerequisite to generate CCVs. Strikingly, in this system at near physiological concentrations of reagents, epsin-1 alone does not have the propensity for scission but is required for bud formation, whereas AP-2 and clathrin are not sufficient. Thus, our study reveals that epsin-1 is an important factor for the maturation of clathrin coated buds, a prerequisite for vesicle generation.